Pleione jinhuana (Arethuseae; Epidendroideae; Orchidaceae), a new species from China based on morphological and DNA evidence - Jiang, Ming-Tao; Wu, Sha-Sha; Liu, Zhong-Jian; Lan, Si-Ren (Phytotaxa, 2018)
Pleione jinhuana, a new orchid from China, is illustrated and described based on morphological and phylogenetic evidence. Detailed morphological comparisons between the new species and other members of Pleione indicate that P. jinhuana is similar to P. bulbocodioides and P. formosana but differs in having a lip with an erose apical margin and lateral lobes not enfolding the column. To explore the phylogenetic position of this species, nuclear ribosomal ITS and plastid DNA (matK exon, trnT-trnL spacer, trnL exon and trnL-trnF spacer) were sequenced for P. jinhuana and individuals of P. formosana collected in Taiwan, Fujian and Zhejiang Provinces. The morphological and molecular evidence support the hypothesis that P. jinhuana is a new species.